Impact of Government Regulations on Small Business Performance: A Comparative Study - M Usmany, Alfrin Ernest (IJBLE Scientific Publications Community Inc., 2024)
This study examines the impact of government regulations on small business performance through a comparative analysis of 20 countries. Utilizing quantitative data from reputable sources such as the World Bank's Doing Business reports, OECD Economic Surveys, and the Global Entrepreneurship Monitor, the research identifies key regulatory factors influencing business outcomes. Findings indicate that simplified business registration, flexible labor market regulations, favorable taxation policies, and improved access to credit significantly enhance small business growth, profitability, and innovation. The study also highlights the potential for stringent environmental regulations to drive innovation. The results offer valuable insights for policymakers aiming to create supportive regulatory environments that foster small business success. The study concludes with recommendations for regulatory reforms and suggestions for future research to further understand the dynamic relationship between regulations and small business performance.